Traditional Chinese health secrets the essential guide to harmonious living - Xu, Xuangcai (YMAA, 2001)
Decover Chinese secrets to maintaining health and expanding mental and physical capabilities. Originally published in China, this re-edited edition teaches us to take care of ourselves with simple all-natural remedies and herbal recipes, before the ailments (and doctor's fees) get out of hand